Dynamics of uric acid concentration against the background of early dapagliflozin use in patients with acute decompensation of heart failure - Laura H. Sarieva; Anastasiya E. Poskakalova; Svetlana N. Nasonova; Igor V. Zhirov; Sergey N. Tereshchenko (Consilium Medicum)
Background. Acute decompensation of heart failure (ADHF) is an urgent problem of modern cardiology due to unfavourable prognosis and high frequency of repeated hospitalizations. The risk of acute kidney injury in patients with ADHF, which significantly worsens clinical outcomes, is high, including due to elevated uric acid levels.